O desvelo da vida cotidiana e o trabalho do assistente social - Guazzelli, Amanda (2009)
This research discusses the activity of social worker and the every day life and social subjects with which it works. The profession of social work is treated in participating in the process of production and reproduction of the entire social life, thus participating social workers, the very process of (re) production of social relations, hence the social significance of this profession. As the real work of worker social is mediated and is conformed to the terms of abstract work, we seek to seize and examine the working professional with a view to the fundamental mediation, inspiring us to do that, the productions of Marilda Villela Iamamoto. Everyday life is understood by all the key activities that characterize the (re) production of men, therefore, as an ontological category, treated here by the social ontology of Marx. In this sense, our reflections on everyday life are based on the production of Hungarian philosophers, György Lukács and Agnes Heller, that, in his Marxist phase. The key activities that mark the (re) production of everyday life of the social subjects of this research are work and motherhood. Otherwise, the contents of the actual work of social workers focus on these same activities as, seek professional answers the needs of survival, with privileged access to such training to the domestic sphere of social life of the individuals with whom they work. In this sense, the premise of the research is the vital relationship between the work of social worker and everyday life in these subjects. We interviewed three social workers and two women who were and / or are served by social workers; we conducted three interviews with each of the interviewees. The research process revealed that the social worker participates in the process of (re) production of social relations through participation in the process of (re) production of everyday life of these subjects